The methods and materials of health expectancy - Saito, Yasuhiko (Stat J IAOS, 2014)
Health expectancy is an essential population health indicator and can be used to monitor changes and/or assess differences in population health. This article provides a brief overview of health expectancy and the issues to be considered in operationalizing and interpreting health expectancy. The article introduces the concept of health expectancy, discusses measures used to compute health expectancy, and methods of calculation. The discussion of measures relates health expectancy to the concept of “health” and clarifies that values of health expectancy depend on how “health” is defined. Software available to compute health expectancy including IMaCh, SPACE and ELECT are also briefly introduced.